Cardiovascular diseases: from epidemiology to nutritional interventions - Zampelas, Antonis (Henry Stewart Talks, 2008)
Dietary treatment, small overview of the process of atherosclerosis, effects of dietary fat and cholesterol on risk factors, the influence of whole grains, dietary pattern and alcohol, the role of sodium, the importance of fruits and vegetables, the uncertainties regarding vitamin and mineral supplementation, to role of phytosterols and phytostanols, principles of management of hyperlipidemias by dietary means
Archived at 2021/02/25